Pain Perception and Migraine - Russo, Antonio; Coppola, Gianluca; Pierelli, Francesco; Parisi, Vincenzo; Silvestro, Marcello; Tessitore, Alessandro; Tedeschi, Gioacchino (Frontiers in Neurology, 2018)
Background: It is well-known that in the perception of pain not only an inter-individual but also an intra-individual difference exists, and this is especially true in migraine, an elusive painful disorder of the head. Although during the last decades, electrophysiology and neuroimaging techniques have greatly contributed to the understanding of mechanisms involved in migraine, the exact characteristics of pain threshold and the pain intensity perception seem far to be determined and still matter of debate. Objective: The aim of this review is to provide a comprehensive overview of the findings offered by clinical, electrophysiological and functional neuroimaging studies aimed to investigate, using pain threshold and pain intensity perception assessments, changes during the various phases of the so-called migraine cycle and in different migraine phenotypes. Methods: A systematic search for qualitative studies was conducted using as search terms (subject headings and keywords) “migraine”, “pain”, “headache”, “temporal summation”, “quantitative sensory testing”, and “threshold”, alone and in combination. The literature search was updated using the additional keywords “pain intensity”, and “neuroimaging” to identify full-text papers written in English and published in peer-reviewed journals, using the PubMed and Google Scholar databases. In addition, we manually searched the reference lists of all research articles and review articles. Conclusion: Consistent data indicate that pain threshold is lower during the ictal phase than both the interictal phase of migraine and healthy controls in response to pressure and cold, and heat stimuli applied over the cephalic region on the usual headache side. On the other hand, despite methodological limitations of the studies, converging observations support the concept that migraine patients may be characterized by a normal pain intensity perception. Nevertheless, future studies are mandatory in order to longitudinally investigate a large group of patients, before and after pharmacological and non-pharmacological interventions, paying attention to phases of migraine cycle, record clinical parameters of disease severity and chronic medication usage.